Evaluation of the early and late examination in sexually assaulted child - Bora Ozdemir; Osman Celbis (Medicine Science, 2012)
In this paper, we evaluated procedures for performing and timing of the examination in sexually assaulted child. Priority management in admission must be considered for protecting the child’s health, since sexually abused child were already physical and psychological disturbed. We have to avoid receiving repeated history and unnecessary examinations, unless necessary. It almost certain that the management may not complete in a short time, repeated psychological examinations are inevitable in this situation. Examination should be considered as beginning of management and a part of the treatment procedure. Anogenital examination should be performed at early period and at once, and is important to avoid duplication of the same examination. In cases of acute sexual assault, emergent examinations are needed to identify injury, collect forensic evidence, prevent infections and for pregnancy prophylaxis. Since several signs may appear after a certain time in sexual assault, it is appropriate that control examinations should be performed after a period. As a result; while avoiding from repeated examinations, to avoid further trauma in abused child we may cause incomplete examination and elongation of management. One kept in mind that taking history for examination is different from expression of the crime. [Med-Science 2012; 1(1.000): 55-64]